Admissibility of Evidence Obtained as a Result of Issuing an European Investigation Order in a Polish Criminal Trial - Kuczyńska, Hanna (Review of European and Comparative Law, 2021)
This article analyses the admissibility of evidence gathered by the Polish procedural authorities as a result of issuing an European Investigation Order, on the basis of provisions implemented due to the adoption on the 3th of April 2014 of the Directive of the European Parliament and of the Council regarding the European Investigation Order in criminal matters. This Directive created a mechanism that allows for transfer of evidence between EU Member States. In this text the question will be answered how to deal with results of investigative measures that have been legally obtained in the executing state but despite acting in accordance with the legality principle by both states, happen to be illegal in the issuing Member State. Another discussed problem is how the rules of admissibility of evidence obtained from the result of issuing an EIO work in Poland – or at least how they should operate. The second discussed issue thus will refer to the current provisions in force in Poland regulating the method of dealing with evidence obtained abroad – that is also with evidence transferred from other Member States. It will be shown that they are unclear and may lead to undesirable results. In addition, suggested changes in Polish law will be proposed.